Uptake and Transport of Naringenin and Its Antioxidant Effects in Human Intestinal Epithelial Caco-2 Cells - Zhang, Zhen-Dong; Tao, Qi; Qin, Zhe; Liu, Xi-Wang; Li, Shi-Hong; Bai, Li-Xia; Yang, Ya-Jun; Li, Jian-Yong (Frontiers in Nutrition, 2022)
Naringenin, a flavanone, has been reported for a wide range of pharmacological activities. However, little has been reported on its absorption, intestinal uptake, transport profiles, and its antioxidant effects. The purpose of this study was to explore the uptake, transport and antioxidant effects of naringenin in vitro. Cell transmembrane resistance, lucifer yellow transmission rate, and alkaline phosphatase activity were used to evaluate the successful construction of Caco-2 cell model. The results revealed that the uptake and transport of naringenin were time- and concentration- dependent. Different temperatures (37℃ and 4℃) had a significant effect on the uptake and transport of naringenin. Verapamil, potent inhibitor of P-glycoprotein, significantly diminished naringenin transport from the apical to basolateral side. The results revealed that naringenin was a moderately absorbed biological macromolecule and can penetrate Caco-2 cells, mainly mediated by the active transport pathway involved in P-glycoprotein. At the same time, naringenin pretreatment could significantly increase the viability of H2O2-induced Caco-2 cells. A total of 24 metabolites were identified as biomarkers by using metabolite analysis of cell based on ultra-performance liquid chromatography-tandem mass spectrometry, which belonged to alanine, aspartate and glutamate metabolism, histidine metabolism, taurine and hypotaurine metabolism, pyruvate metabolism, purine metabolism, arginine biosynthesis, citrate cycle (TCA cycle), riboflavin metabolism, and D-glutamine and D-glutamate metabolism. We concluded that naringenin may play a more important role in preventing oxidative stress induced intestinal diseases.